Parvana's journey - Ellis, Deborah, 1960- (Ellis, Deborah, 1960- Breadwinner series, 2015)
Parvana, disguised as a young boy, continues her journey through the Afghanistan countryside looking for what remains of her family and is joined along the way by three other orphans of the war-torn country.